Chemical Composition and Corrosion—Contributions to a Sustainable Use of Geothermal Water - Ioana Maior; Gabriela Elena Badea; Oana Delia Stănășel; Mioara Sebeșan; Anca Cojocaru; Anda Ioana Graţiela Petrehele; Petru Creț; Cristian Felix Blidar (Energies, 2025)
The utilization of geothermal resources as renewable energy is a subject of interest for the regions that possess these resources. The exploitation of geothermal energy must consider local geological conditions and an integrated approach, which should include practical studies on the chemistry of geothermal waters and their effect on thermal installations. Geothermal waters from Bihor County, Romania, have a variable composition, depending on the crossed geological layers, but also on pressure and temperature. Obviously, water transport and heat transfer are involved in all applications of geothermal waters. This article aims to characterize certain geothermal waters from the point of view of composition and corrosion if used as a thermal agent. Atomic absorption spectroscopy (AAS) and UV–Vis spectroscopy were employed to analyze water specimens. Chemical composition includes calcite (CaCO3), chalcedony (SiO2), goethite (FeO(OH)), and magnetite (Fe3O4), which confirms the corrosion and scale potential of these waters. Corrosion resistance of mild carbon steel, commonly used as pipe material, was studied by the gravimetric method and through electrochemical methodologies, including chronoamperometry, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization method, and open circuit potential measurement (OCP). Statistical analysis shows that the medium corrosion rate of S235 steel, expressed as penetration rate, is between 0.136 mm/year to 0.615 mm/year. The OCP, EIS, and chronoamperometry experiments explain corrosion resistance through the formation of a passive layer on the surface of the metal. This study proposes an innovative methodology and a systematic algorithm for analyzing chemical processes and corrosion phenomena in geothermal installations, emphasizing the necessity of individualized assessments for each aquifer to optimize operational parameters and ensure sustainable resource utilization.